Computational study of the inhibitory potential of Gongronema latifolium (benth) leave on farnesyl pyrophosphate synthase, a target enzyme in the treatment of osteoporosis. A molecular modelling approach - Samuel O. Olubode; Bankole Mutolib; Precious Ayorinde Akinnusi; Wasiu A. Salaudeen; Kehinde I. Ojubola; Olayinka S. Adanlawo; Abigail Oluwakemi Ayodele; Adefunke O. Ogunlade; Abdullahi A. Aderemi (Islamic Azad University, Shahrekord Branch, 2022)
Background & Aim: Osteoporosis is an increasing medical threat which is referred to as a systemic skeletal disorder that is characterized mainly by low bone mass and microarchitectural wear of bone tissue and strength, which eventually results in an increase in the fragility of bone and makes bone to be susceptible to fracture. Osteoporosis is known globally as a severe health problem affecting approximately 200 million people worldwide. Therefore, a pharmacological solution is urgently needed. Studies have shown that farnesyl pyrophosphate synthase is a crucial enzyme in the mevalonate pathway that causes bone resorption, thus serving as a key pharmacological target. Experimental: Gongronema latifolium's (Benth) phytoconstituents were screened against the mevalonate pathway enzyme farnesyl pyrophosphate synthase computationally using molecular docking, pharmacokinetics screening and Molecular Mechanics/Generalized Born Surface Area approach to identify compounds with the better inhibitorypotentials against this target in this study. Results: The study resulted that five compounds; hyperoside, rutin, epigallocatechin-3-gallate, kaempferol-3-arabinoside, and isoquercetin show a better inhibitory potential by binding to the active site of farnesyl pyrophosphate synthase compared with a co-crystalized ligand. These hit compounds were further subjected to pharmacokinetics studies to predict their drug-likeness and toxicity characteristics which show that all hit compounds except Rutin are drug-like leaving Kaempferol-3-Arabinoside as the most drug-like hit compound compared to the co-crystallized ligand. Recommended applications/industries: This study suggests that G. latifolium leaf could be a good plant source for a drug-like compound that may treat osteoporosis by inhibiting the farnesyl pyrophosphate synthase, in the mevalonate pathway, thereby stopping bone resorption.